Az 1887 és 1905 közötti országgyűlési választások eredményeinek statisztikai vizsgálata - Pap, József (Közép-Európai Közlemények, 2009)
The aim of this study was to analyse the parliamentary elections between 1884 and 1905. We made the list of MPs with mandates and mentioned the issues of fluctuation of the MPs as well. On the basis of the electoral results an election map was made. Data were processed by using cluster analysis. Clusters were compared to relations of the nationalities. Finally we presented the results of the parties regarding the ethnical relations. During our work we made three maps. The first presents the proportion of the Hungarian voters in the total population, the second presents the connection between the ethnical construction of the administrative areas and the ethnical composition of the voters, the third presents the classification of the cases of the constituencies indicating the areas inhabited by Hungarian majority.